Wczesna edukacja i opieka nad dzieckiem jako wyzwanie dla polityki społecznej z perspektywy Unii Europejskiej - Elżbieta Subocz (Problemy Wczesnej Edukacji)
For two decades we have been observing a lot of interest in the issues of early childhood education and child care in the European Union. Child well-being is seen as an investment in the future of Europe. The article is an attempt to answer the following questions: what are the EU’s views in the field of early childhood education and care? What activities does the European Union take to improve the availability and quality of early childhood education and care for the youngest generation in the Member States? How do the Member States implement the EU’s recommendations?